Measurement of lipid transfer proteins in genetically engineered maize using liquid chromatography with tandem mass spectrometry (LC-MS/MS). Issue 4 (2nd October 2017) - Hill, Ryan C.; Wang, Xiujuan; Schafer, Barry W.; Gampala, Satyalinga Srinivas; Herman, Rod A.
ABSTRACT: Endogenous allergenicity evaluation is a required part of the risk assessment for genetically engineered (GE) crops. Although maize is not considered a major allergenic food, a lipid transfer protein (Zea m 14) in maize grain has been identified as a potential IgE-mediated food allergen. Currently, the relationship between allergen exposure and risk of sensitization is not well understood. Hence, reliable quantitative methods are useful for determining the natural range and variability of allergen levels across multiple geographies and genetic backgrounds. A LC-MS/MS analytical method was developed and validated in our laboratory to quantify Zea m 14 in grain from 2 GE maize hybrids and 20 non-GE maize hybrids. The measured Zea m 14 levels in GE maize grain and conventional non-GE maize grain ranged from 146.87 to 574.93 ng/mg across 16 field sites located in the United States and Argentina. The method accurately quantified endogenous Zea m 14 from maize grain and results show Zea m 14 levels in the GE maize varieties were within the natural variation observed in traditionally bred non-GE maize.